"Я заглянул в лицо небес": стихи о Боге и Руси / Иван Алексеевич Бунин - Бунин Иван Алексеевич (Проект "Энциклопедия малыша", 2004)
Экземпляры: ф. 2 (20101122) / Инвентарный номер: 96760 / Цена: 40.00 / Авт.знак: Б 91 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)1